Strategic directions for strengthening economic security and developing competitive advantages of construction companies - HOIKO, Anatolii; TSYFRA , Tetiana; BESEDA, Maksym; PALAHITSKYI , Viktor; TYMOFIEIEV, Dmytro (Ways to Improve Construction Efficiency, 2024)
In the current conditions of the development of the Ukrainian economy, the competitiveness of construction enterprises is a key criterion of their effectiveness, which determines market stability and prospects for further development. Ensuring a high level of competitiveness depends on the ability of the enterprise to produce products that meet modern requirements for quality, manufacturability and costs for its creation and implementation. At the same time, existing problems associated with an insufficient level of management, the lack of clear strategies, economic goals and evaluation criteria, significantly complicate the task of achieving competitive advantages. It has been studied that to effectively increase competitiveness, it is necessary to implement systemic measures: update technologies and equipment, conduct regular marketing research, assess the strengths and weaknesses of competitors, determine one's own potential and choose the most profitable competitive strategies. It has been determined that a promising direction for increasing competitiveness is the introduction of functional innovations that optimize the organization of the production process, reduce costs and improve product quality. It is proposed to pay special attention to benchmarking as an effective tool for increasing competitiveness, which allows enterprises to systematically study and implement the best practices of leading companies in the industry, compare their own results with reference indicators, and constantly improve business processes. A comprehensive methodology for assessing the competitiveness of enterprises is proposed, which is based on a formalized mathematical apparatus and allows taking into account the specifics of enterprises, the availability of information, and the peculiarities of the market, which will contribute to increasing efficiency and profitability in conditions of increased competition.